2001
DOI: 10.2135/cropsci2001.4141130x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Net Nitrate Uptake by Ammonium in Pima and Acala Cotton Roots

Abstract: This study was conducted to determine whether the inhibition of net NO−3 uptake by NH+ 4 in cotton roots is due to inhibition of NO− 3 influx per se, and/or enhancement of efflux. Two cotton species, Pima (Gossypium barbadense L.) and Acala (G. hirsutum L.), which differ in NO− 3 influx and efflux, were used. Seedlings were grown hydroponically for 10 to 11 d and then induced for NO− 3 uptake with 0.01, 0.10, or 1.0 mM NO− 3 Net uptake was determined by following NO− 3 depletion from uptake solutions, containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Such a greater reliance on NO À 3 than on NH þ 4 and preference for NO À 3 over NH þ 4 is unlikely in our study area. First, the inhibitory effect of NH þ 4 on NO À 3 utilization is well known to prevail among microbes (Rice & Tiedje, 1989), phytoplankton (reviewed by Dortch, 1990), and vascular plants (Kronzucker et al, 1999;Aslam et al, 2001;Wang & Macko, 2011). Evidence from phytoplankton showed that the inhibitory effect occurs at NH þ 4 concentrations higher than c. 1 lM (a concentration much lower than NH þ 4 concentrations in precipitation and soil solutions) (Dortch, 1990).…”
Section: Researchmentioning
confidence: 99%
“…Such a greater reliance on NO À 3 than on NH þ 4 and preference for NO À 3 over NH þ 4 is unlikely in our study area. First, the inhibitory effect of NH þ 4 on NO À 3 utilization is well known to prevail among microbes (Rice & Tiedje, 1989), phytoplankton (reviewed by Dortch, 1990), and vascular plants (Kronzucker et al, 1999;Aslam et al, 2001;Wang & Macko, 2011). Evidence from phytoplankton showed that the inhibitory effect occurs at NH þ 4 concentrations higher than c. 1 lM (a concentration much lower than NH þ 4 concentrations in precipitation and soil solutions) (Dortch, 1990).…”
Section: Researchmentioning
confidence: 99%
“…Many studies have shown that the presence of NH 4 + in nutrient media leads to decreased NO 3 − uptake, again probably involving the feedback loops controlling the NO 3 − uptake system (Breteler and Siegerist, 1984;Kronzucker et al, 1999;Aslam et al, 2001;Glass, 2003). An NH 4 + inhibition of NO 3 − uptake would explain the cation to anion ratio being just above 1.0 in +P control plants.…”
Section: Discussionmentioning
confidence: 99%